QP "DCT and Wavelet transfer (HAAR, DB)" quantization implementation in the frequency domain - et. al., Jaafar M. Al-alghabban, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper compares between three image compression Discrete Cosine Transform (DCT) and Wavelet Transform (Haar, DB), and combines the two of them. The new block incorporates the DCT benefits in which it functions flawlessly with highly correlated data. In addition to, the benefits of the transformation of Haar that provide preferable ends for images exhibiting rapid gradient variations. DCT has been implemented to the upper left corner of the block. Haar has been applied to the remaining parts of the block. The whole process introduces an error in the signal which increases as we raise the value of QP. Finally, is the inverse transform which takes the quantized/de-quantized coefficients and reconstruct the values in the pixel domain. This was done by using proper MATLAB function